PENGARUH BRAND AWARENESS DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SEPATU MEREK SKECHERS - Amano, Mogi; Ilhami, Mardhiyah Dwi (UM. Bengkulu, 2025)
Consumer purchase decisions are influenced by various factors, including brand awareness and brand image. This study aims to analyze the influence of brand awareness and brand image on the purchase decisions of Skechers shoes at the Sport Station shoe store in Bencoolen Mall, Bengkulu City. This research employs a quantitative method with a survey approach. The study's respondents consisted of 84 consumers of the Sport Station store. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The results show that brand awareness has a positive and significant effect on purchase decisions. This means that the higher the consumer awareness of the Skechers brand, the greater the likelihood of purchasing the product. Additionally, brand image also has a positive and significant impact on purchase decisions, indicating that a strong brand image can enhance consumer interest and trust in choosing Skechers products. This study confirms that brand awareness and brand image are crucial factors in influencing consumer purchase decisions. Therefore, marketing strategies that strengthen brand awareness and build a positive image of Skechers should be continuously optimized to increase consumer purchases. Keywords: Brand Awareness, Brand Image, Purchase Decision